The Effectiveness of Media Technology Assisted Webbed Thematic Learning Model on Learning Outcomes in Social Studies, Healthy Food Theme of Students in Class V - didisyahrir didisyahrir; Firman; Desyandri (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Social studies learning is a lesson in people's lives that can be used as a source of social life for the benefit of learning by using social science concepts. The first reason underlying this is because of the empirical background. Students in the class are in the early age range who still see everything as a whole so that their learning still depends on concrete objects and the experiences they experience. The second reason, namely the implementation of learning in SD which is separate for each subject will result in less developing children to think holistically. The third reason is that there are problems in the early and high grades. In addition, the approach or learning method used by teachers tends to emphasize the use of the lecture method and skills in using technology that are not optimal as learning tools or media in class, thus making learning monotonous and students bored and there is still a lack of research being conducted. The aim is to determine the quality of social studies learning for fifth grade students at SDN 15 Patamuan by applying the webbed-type thematic learning model assisted by motion media technology, knowing the quality of social studies learning for fifth grade students at SDN 15 Patamuan by applying the webbed-type thematic learning model assisted by technology without using motion media and can determine the differences in the quality of social studies learning.